Functional Balance and Electrophysiological Responses to Synchronized Lifestyle Modification and Physiotherapy in Type 2 Diabetic Peripheral Neuropathy - Rubab Rameez; Fatima Iqbal; Ayesha Zafar; Aysha Mushtaq; Zara Shaukat; Mehvish Ashfaq, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Diabetic peripheral neuropathy impairs proprioception, postural control, and mobility. Functional recovery may occur before measurable normalization of large-fiber electrophysiology, but few trials have evaluated balance and nerve-conduction outcomes together. Objective: To compare the effects of synchronized lifestyle modification, supervised physiotherapy, and their combination on functional balance and lower-limb sensory and motor nerve-conduction parameters in adults with type 2 diabetic peripheral neuropathy. Methods: In this four-arm randomized controlled trial, 120 adults aged 40–75 years were allocated to control (n=60), synchronized lifestyle modification (n=20), synchronized lifestyle modification plus physiotherapy (n=20), or physiotherapy (n=20). Interventions continued for 12 weeks. Balance was assessed using the Berg Balance Scale (BBS). Bilateral sural and peroneal sensory and peroneal and tibial motor nerve peak latency, amplitude, and conduction velocity were evaluated. BBS change scores were compared by one-way analysis of variance followed by Tukey testing. Nerve-conduction outcomes were assessed using the original repeated-measures analysis. Results: Mean BBS change was −0.13±0.79 in control, +1.70±0.47 with lifestyle modification, +1.95±0.51 with the combined intervention, and +2.40±0.82 with physiotherapy. The between-group difference in change was significant (F(3,116)=94.37, p<0.001, η²=0.709); every active intervention outperformed control. Physiotherapy produced a greater improvement than lifestyle modification alone (mean difference 0.70 points, 95% CI 0.11–1.29; p=0.013), whereas the combined intervention did not differ significantly from either active intervention. Nerve-conduction measures showed small favorable directional changes in active groups, but no statistically significant between-group electrophysiological effects were detected. Conclusion: Twelve weeks of synchronized lifestyle modification and/or physiotherapy improved balance, while nerve-conduction parameters remained statistically unchanged. Functional gains may precede detectable electrophysiological recovery, although the absolute BBS changes were modest.